EFEKTIVITAS PENGELOLAAN DAN TRANSPARANSI DANA DESA DI DESA SIDOHARJO KECAMATAN TOLANGOHULA KABUPATEN GORONTALO - Lantowa, Felmi D.; Sadikin, Nurjanah (JSAP : Journal Syariah and Accounting Public, 2021)
This study aims to determine the Effectiveness of Village Fund Management and Transparency in Sidoharjo Village, Tolangohula District, Gorontalo Regency. This type of research uses descriptive research with a qualitative approach according to Arif (2015:21). The results of this study are that the Management and Transparency of Village Funds in Tolangohula District, Gorontalo Regency are in accordance with Permendagri Number 20 of 2018 where the planning, implementation, administration, reporting and accountability of Village Funds are in accordance with the provisions of Village Fund management as regulated in Permendagri No. 20 of 2018, but in terms of planning, Sidohardo Village still does not routinely involve the community in the village fund planning deliberation process as a form of supervision of the Village Government, in terms of implementation there are often changes to the budget made and in terms of transparency the management of Village Funds has been implemented. implemented by the Sidohardjo Village Government but there is still a need for government evaluation of the community regarding the delivery of Village Fund Management to the community properly and clearly in order to create transparent and accountable financial reports, this is as the theory expressed by Krina (2015:17).